Motivational drivers for the adoption of green energy: The case of purchasing photovoltaic systems. Issue 5 (20th May 2019) - Arroyo, Pilar; Carrete, Lorena
Abstract : Purpose: The purpose of this paper is to propose and empirically test a model where different motivational drivers are used to stimulate the intention of individuals to purchase green energy. Design/methodology/approach: The goal-framing theory was used as the theoretical basis to design motivational statements that activate different self-goals driving the intention to adopt green energy. A field experiment was performed to investigate the influence of three different goal triggers on the intention of purchase green energy, specifically solar systems, among households living in a major city located in the central part of Mexico. The effect of demographics, environmental consciousness and perceived risk associated to the technology functionality was also considered in explaining the probability of purchase of a photovoltaic system in a short (one year) and medium (five years) terms. Findings: The goal trigger grounded on normative motivations is the most influential on the probability of adoption of a photovoltaic system. However, the socioeconomic level of the household moderates the effect this type of goal trigger has on the intention of purchase a photovoltaic system. Individuals with a high socioeconomic level significantly increase their intention of purchase this green technology if motivated by a normative goal. On the contrary, individuals with a medium socioeconomic level are mostly motivated by goal triggers grounded on economic benefits. Research limitations/implications: This study was circumscribed to a particular city of Mexico. Replication of the experiment in cities of other developing countries with contrasting sociotechnical contexts and the consideration of other green behaviours and explanatory variables is relevant to confirm and complement the results of this research. Practical implications: The cost of photovoltaic systems represents a major barrier to the growth of the Mexican market of this renewable energy. Therefore, the promotion strategy for solar energy must be accompanied by the design of appropriate motivational drivers depending on the socioeconomic level of the segment and the time for the investment. Additionally, public and private strategies to decrease the cost of the technology and financing programs for individual and community projects are recommended. Social implications: The willingness to use green energy and contribute to the protection of the environment should spring from within consumers. To upscale the solar energy market, it is relevant to understand the dominant goals of individuals when taking the decision to purchase green energy. Originality/value: This study contributes to the extant research in green marketing by proposing and testing a new interpretative framework to examine how the benefits of green energy activate the self-goals of consumers, thus influencing their intentions of adoption of green energy. A theoretical model is proposed by constructing "goal-triggers" grounded on the goal-framing theory and empirically testing in the specific case of explaining the intention of purchasing photovoltaic systems in Mexico.